2018
DOI: 10.1101/403865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oscillatory infrasonic modulation of the cochlear amplifier by selective attention

Abstract: 21 Evidence shows that selective attention to visual stimuli modulates the gain of 22 cochlear responses, probably through auditory-cortex descending pathways. At the cerebral 23 cortex level, amplitude and phase changes of neural oscillations have been proposed as a 24 correlate of selective attention. However, whether sensory receptors are also influenced by 25 the oscillatory network during attention tasks remains unknown. Here, we searched for 26 oscillatory attention-related activity at the cochlear recep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 36 publications
6
30
1
Order By: Relevance
“…In contrast, Dragicevic et al (2019) reported significant correlations between the oscillatory DPOAE signal and cortical oscillations at low frequencies (< 10 Hz) mainly when attention was switched from the visual to the auditory modality.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…In contrast, Dragicevic et al (2019) reported significant correlations between the oscillatory DPOAE signal and cortical oscillations at low frequencies (< 10 Hz) mainly when attention was switched from the visual to the auditory modality.…”
Section: Discussionmentioning
confidence: 75%
“…In line with previous studies that found reduced levels of OAEs in subjects attending to a visual task, our results resemble an elevation of the to-be-attended acoustic stimulus during acoustic selective attention (Froehlich, Collet, Valatx, & Morgon, 1993;Meric & Collet, 1992;Puel, Rebillard, Bonfils, & Pujol, 1989;Wittekindt et al, 2014;see Smith et al (2012) for an exception). Particularly, one study consistently reported similar amplitude modulations at low frequencies (< 7 Hz; Dragicevic et al, 2019). Yet, thus far, all studies on humans that have investigated effects of attention on the cochlea in cue-target periods utilized different types of evoked OAEs (EOAE) and distortion product OAEs (DPOAE).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations